Reaching, Retaining, and Releasing Post-College Emerging Adults: Profiles of Evangelical Congregations With Extraordinary Levels of Older Emerging Adult Participation - Gibson, Barry (Christian education journal, 2025)
Within the vast majority of local churches throughout the United States, emerging adults (i.e., 18–29-year-olds) have tended to be poorly represented. With significantly increasing numbers of emerging adults over the past two decades identifying as religiously unaffiliated, not even evangelical congregations—which have historically done somewhat better with this demographic than other Christian traditions—are insulated from this accelerating phenomenon. In contrast to those broader trends, a cohort of multigenerational evangelical churches have experienced an extraordinary level of post-college emerging adult (i.e., 22–29-year-olds) participation. Grounded in the findings of a phenomenological study, this project identifies common elements of those congregations that are seeking to reach, retain, and release older emerging adults. Furthermore, a path forward is proposed for congregational leaders interested in shepherding their churches to more effectively engage and disciple 22–29-year-olds.